The Effect of Procedural Justice and Distributive Justice on Satisfaction of Performance Appraisal System: A Study of Bank Islam's Employees - Aiman, Fadzil (2010)
Employee performance appraisal is common among organizations in Malaysia including the banking industry. Instead of being an isolated bi annual program, appraisals are but one component in the overall process of performance management. According to Robert Bacal, (1999) performance management is an ongoing communication process, undertaken in partnership, between an employee and his or her immediate supervisor that involves establishing clear expectations and understanding about the jobs to be done. The objective of this research is to find the effect of procedural justice and distributive justice on satisfaction of performance appraisal system that has been practised at Bank lslam Malaysia Berhad. The underlying hypotheses of this research are "There is a significant relationship between procedural justice and employees satisfaction with performance appraisal system in Bank lslam Malaysia Berhad" and "There is a significant relationship between distributive Justice and employee satisfaction with performance appraisal system in Bank lslam Malaysia Berhad". Data were obtained via a survey questionnaire from 102 participants from BlMB branches in Kedah, Perlis and Penang. The findings of the study accept both the research hypotheses.